Development of a Zero-Bias Detector Based on T-Type Structure - Xiaobo Zhang; Jin Meng; Jingtao Zhou; Baijun Zhang; Zenghui Liu; Zexing Yuan (IEEE Access)
The detector plays a crucial role in terahertz (THz) receiving systems, converting weak high-frequency signals into low-frequency or direct current signals that are easier to process. This paper proposes a zero-bias Schottky diode THz detector based on a T-shaped structure. The design is based on the InGaAs/InP material system and achieves efficient detection at 500 GHz. Experimental results show that the voltage responsivity of the detector reaches over 2000 V/W at 500 GHz, demonstrating excellent performance. This paper provides a detailed introduction to the design concept, working principle, and experimental results of the detector, which lays the device foundation for the development of terahertz focal plane imaging systems and provides support for future terahertz applications in higher frequency bands.